Assessing ODL Teachers/Tutors’ Opinion about Inclusion of Children with Emotional, Social and Behavioural Difficulties in ODL - Zahid Majeed, (PJE, 2023)
In Pakistan about 2.49% of population is with special needs including hearing, visual impairment, mentally challenged, physically handicapped and multiple handicaps. Open and Distance Learning is most suitable and accommodative mode for them so much of them are getting education through ODL mode. The study aim was to determine the e-tutors arrogances to include students having emotional, social and behavioural difficulties (ESBD) seeing the impact of physical age, know-how, academic education/degrees and the help they had from AIOU. Researcher selected 200 e-tutors/e-instructors as sample for the study and most ofthem from Islamabad region.